ANALISIS RISIKO PADA INCINERATOR PENGOLAHAN LIMBAH MEDIS PT. PENGELOLA LIMBAH KUTAI KARTANEGARA,SAMBOJA – KALIMANTAN TIMUR - Hardiyono, Hardiyono; Arifin, Syamsul; Kelana, Andri Indra (Program Studi Kesehatan dan Keselamatan Kerja, 2021)
Risk assessment was carried out at the medical waste combustion process facility using Incinerator. The method used in this research is HAZOP. This research is descriptive qualitative or observation research. The results of this study provide an overview of the risk level of the process at the Incinerator facility, where the highest risk level is in the process of Rotary Kiln Chamber 1, Chamber 2, Heat Exchanger, Water scrubber, Cyclone, Induce draft Fan, Sampling Point, and Exhaust stack. The level of risk is derived from probability and severity. In addition, recommendations are produced as materials for companies to make design improvements so that identified risks can be minimized. Keywords : Incinerator, HAZOP, Risk